Peculiar purulence: Hypervirulent Klebsiella pneumoniae causing pyomyositis. (December 2017) - Mgbemena, Okechukwu; Serota, David P.; Kumar, Sonali; Wozniak, Jessie E.; Weiss, David S.; Kempker, Russell Ryan
Highlights: Hypervirulent Klebsiella pneumoniae is characterized by a hypermucoviscious phenotype. The most common pyogenic syndrome is bacteremia and liver abscess. The organism's increased virulence relies on a thickened polysaccharide coating to avoid phagocytosis. Abstract: This report describes the first confirmed case of isolated pyomyositis caused by a hypervirulent strain of Klebsiella pneumoniae . Pyomyositis is almost universally caused by gram-positive organisms and while the recent emergence of invasive disease due to hypervirulent K. pneumoniae has been well documented, the most common clinical manifestation reported is liver abscess. The K. pneumoniae isolate in our case had a hypermucousviscous phenotype as demonstrated by a positive string test and was confirmed to be hypervirulent with molecular testing. Documenting the extrahepatic manifestations of hypervirulent Klebsiella pneumoniae strains is important to increase clinical awareness and in guiding empiric antibiotic regimens.